Using event-driven lightweight DSC-based agents for MAS modelling. (23rd April 2010) - Fortino, Giancarlo; Garro, Alfredo; Mascillaro, Samuele; Russo, Wilma
To date several agent models and related programming frameworks have been introduced for developing distributed applications in terms of multi-agent systems in open and dynamic environments. Among them, those based on lightweight architectures, asynchronous messages/events and state-based programming such as JADE, Bond and Actors have demonstrated great effectiveness for modelling open and distributed software systems. In this paper, we propose the event-driven lightweight distilled statecharts-based agent (ELDA) model which is based on the same fundamentals of the aforementioned agent models and frameworks, and provides a more effective design enabled by: a Statecharts-based specification of the agent behaviour, multiple coordination spaces for local/remote inter-agent and agent/non-agent-component interactions, and a coarse-grained strong agent mobility. A MAS based on the ELDA model can be easily designed through the ELDA meta-model and programmed through a Java-based implementation of the meta-model (ELDAFramework). Visual programming and automatic code generation of the MAS under-development is supported by an Eclipse-based visual tool (ELDATool). The produced MAS code can be executed by a discrete-event simulator framework (ELDASim) which allows for the validation of the MAS under-development. A simple yet effective case study is provided to exemplify the proposed model and its related tools.